(untitled) (Research, Society and Development, 2021)
The eyebrow dermopigmentation procedure has a great influence on self-esteem in cancer patients, alleviating psychological aspects that may have been affected by the severe treatment of cancer and its consequences. Thus, dermopigmentation of the eyebrows is an important procedure, much sought after by patients whon seek to achieve this achievement, in order to raise self-esteem, in addition to renewing looks and smiles. Objective to analyze the influence of eyebrow micropigmentation on the self-esteem of cancer patients. A literature review was carried out, with data collection through electronic databases, such as: Scientific Electronic Library Online – Scielo, Bireme, and Academic Google and LILACS Scientific and Technical Literature of Latin America and the Caribbean/VHL – Library Virtual in Health. The findings of this research demonstrate the impact that dermopigmentation has on self-esteem and improvement in the quality of life of cancer patients, also bringing knowledge to readers about the importance of dermopigmentation as an effective procedure that can satisfy the physical and aesthetic of individuals. It is concluded that micropigmentation is an efficient resource to reconstruct the flaw in the eyebrows of patients whon lost hair due to chemotherapy treatment. New studies about the procedures are necessary and important.